Are all Chinese shoppers the same? Evidence of differences in values, decision making and shopping motivations between the Han majority and other minorities in China. (September 2018) - Yang, Song; Ding, Shiqing; D'Alessandro, Steven
Abstract: Many retailing and marketing studies have treated China as an ethnically homogenous country and ignored the differences in consumer values and shopping behavior among its various ethnic groups. The current research takes an important first step and explores the differences between the Chinese ethnic minorities and the mainstream Han majority with respect to consumer values (materialism, ethnocentrism and cosmopolitanism) and eight consumer shopping styles. In a study of 405 Han and other minority collected from students in Yunnan Province it was found that the ethnic minorities were less materialistic but more ethnocentric than the ethnic majority Han Chinese. The two ethnic groups were similar in cosmopolitan orientation and share four out of six shopping styles. The ethnic minorities as opposed to the Han Chinese are less likely to have hedonic shopping motivations. Path analysis suggested the overall importance of materialism in driving western shopping behavior, but important differences across ethnic groups occurred with ethnocentrism for the minorities influencing a desire for in-group representations of fashion and recreational shopping, whilst for majority Han, interest in cosmopolitism does drive a desire for quality, but less interest in fashion and recreational shopping, possibly because such styles may already be part of the Chinese way of life. Retailers in China therefore need consider in some provinces the ethnic composition of the region and cater for differing motivations across sub-cultures. They should not assume that all Chinese are equally materialistic and ethnocentric in their decision making.